Digitalisasi Produk UMKM Berbasis E-Katalog untuk Meningkatkan Komersialisasi Pemasaran di Lingkungan Komunitas UMKM PADUKA - Irianto, Wahyu Sakti Gunawan; Widiyaningtyas, Triyanna; Sujito, Sujito; Habibi, Muhammad Afnan; Syah, Abdullah Iskandar; Abdul Hadi, Afif; Fuadi, Ahmad (Bulletin of Community Engagement, 2023)
The Indonesian economy has traditionally relied heavily on the vital contributions of Micro, Small, and Medium Enterprises (MSMEs) to support economic growth and national development. MSMEs not only create jobs but also drive economic growth, especially after economic crises. This community engagement focuses on the Kasembon Subdistrict in Malang Regency and involves the PADUKA MSME Community. In this program, the introduction of an E-Catalog is presented as a solution to improve the marketing of MSME products. The results show that the implementation of the E-Catalog has enhanced the efficiency of product marketing, facilitated access to product information, and provided benefits to consumers. However, challenges related to technology adaptation and diverse understandings need to be addressed. Continuous support and capacity-building in the form of training and mentoring are necessary to ensure the sustainability of this program. This initiative underscores the significant potential of technology in advancing MSMEs and emphasizes the need for a sustainable approach to drive local economic growth. Keywords: E-Catalog, Community Engagement, Economic Growth, Product Digitalization